2020
DOI: 10.3389/fmolb.2020.00217
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Sphingomyelinase-2 (NSM 2) Controls T Cell Metabolic Homeostasis and Reprogramming During Activation

Abstract: Neutral sphingomyelinase-2 (NSM2) is a member of a superfamily of enzymes responsible for conversion of sphingomyelin into phosphocholine and ceramide at the cytosolic leaflet of the plasma membrane. Upon specific ablation of NSM2, T cells proved to be hyper-responsive to CD3/CD28 co-stimulation, indicating that the enzyme acts to dampen early overshooting activation of these cells. It remained unclear whether hyper-reactivity of NSM2-deficient T cells is supported by a deregulated metabolic activity in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Several studies imply that also neutral sphingomyelinases are important in T cell activation ( 100 , 101 ). These studies demonstrated that inhibition of neutral sphingomyelinases interfered with lymph node homing and adhesion of T cells to activated endothelial cells ( 99 , 100 ).…”
Section: Sphingolipids In Autoimmune Lymphocyte Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies imply that also neutral sphingomyelinases are important in T cell activation ( 100 , 101 ). These studies demonstrated that inhibition of neutral sphingomyelinases interfered with lymph node homing and adhesion of T cells to activated endothelial cells ( 99 , 100 ).…”
Section: Sphingolipids In Autoimmune Lymphocyte Activationmentioning
confidence: 99%
“…Thus, deletion of neutral sphingomyelinase-2 resulted in hyper-responsivity of T cells upon stimulation via CD3/CD28 ( 99 , 100 ). This effect seems to be mediated by an increased metabolic activity with an accumulation of ATP in mitochondria and higher basal glycolytic activity in lymphocytes upon downregulation of neutral sphingomyelinase-2 ( 101 ). Whether down-regulation of neutral sphingomyelinase-2 results in an altered immune response in vivo remains to be determined.…”
Section: Sphingolipids In Autoimmune Lymphocyte Activationmentioning
confidence: 99%
“…While ceramide promoted uptake of SARS-CoV-2 virion into epithelial cells, sphingosine-1-phosphate (S1P) receptor activation inhibited the entry [29]. Neutral and acid sphingomyelinase regulate distribution of voltage gated channels, glucose, and lipid uptake [30], therefore, also regulate SARS-CoV-2 spike protein binding and proteolytic processing. Multiple biochemical pathways produce ceramide, with S1P and ceramide interconversion potentially altering the balance of viral transmission.…”
Section: Lipidome Signaturementioning
confidence: 99%
“…While ceramide promoted uptake of SARS-CoV-2 virion into epithelial cells, sphingosine-1-phosphate (S1P) receptor activation inhibited entry [20]. Neutral and acid sphingomyelinase regulate distribution of voltage gated channels, glucose and lipid uptake [21,22] and may, therefore, also regulate SARS-CoV-2 spike protein binding and proteolytic processing. Multiple biochemical pathways produce ceramide, with S1P and ceramide interconversion potentially altering the balance of viral transmission.…”
Section: Mass Spectrometry and Lipidomicsmentioning
confidence: 99%